Hubungan Kecerdasan Emosi Dan Kecemasan Pada Ibu Hamil Di Kota Yogyakarta - Mutya, Mita Fani Tri (Batanang : Jurnal Psikologi, 2022)
During pregnancy there are changes that occur in a woman. Pregnancy can be a source of anxiety. The increasing age of the womb, sometimes makes pregnant women become restless and anxious. Anxiety, fear, worry, and other negative feelings can affect the condition of the mother and fetus in the womb. So that the anxiety that occurs should receive special attention and it is important to be investigated further so that pregnant women can control their emotional conditions and other things. Emotionally intelligent mothers will view pregnancy and the changes that occur as positive things so that they will pass the pregnancy well and comfortably. The study was conducted to determine the relationship between emotional intelligence and anxiety of the first pregnant woman in facing childbirth in Yogyakarta. This type of research is quantitative research. Subjects in the study amounted to 35 pregnant women. The method used for data analysis is Pearson's Product Moment technique. The results obtained show that the correlation obtained is -0.048 at a significance level of 0.009 with probability (p<0.05). This means that there is a negative relationship between emotional intelligence and maternal anxiety in dealing with childbirth.Keywords: emotional intelligence, mother, pregnant, Yogyakarta